PELATIHAN PENGOLAHAN DATA EKONOMI DENGAN EVIEWS BAGI MAHASISWA: PENINGKATAN LITERASI TEKNOLOGI UNTUK KEMANDIRIAN EKONOMI - Bandawaty, Euis; Sanjoyo, Sanjoyo; Sunaryo, Sunaryo; Heny Herawati, Heny Herawati; Sri Lestari, Sri Lestari; Farida Suldina, Farida Suldina; Pangeran Syarif Abdurahman, Pangeran Syarif Abdurahman (Forum Komunikasi Dosen, 2024)
Mastery of data processing technology has become increasingly important, particularly in the data-driven field of economics. EViews is one of the widely used software for statistical and econometric data analysis. This training aims to enhance students' technological literacy in using EViews to support economic self-reliance through improved analytical skills. The activity was conducted offline over two days, involving 50 students from the Faculty of Economics and Business, comprising accounting and management students from Asstafi'iyah Islamic University. The results of the training showed a significant improvement in students' understanding of data processing and their ability to perform regression analysis, hypothesis testing, and economic forecasting. A total of 80% of the participants were able to effectively operate EViews for economic data analysis. This training had a positive impact in preparing students for the workforce and increasing their independence in handling data processing independently.